Exploratory Factor Analysis on Suicidal Tendencies among College Students in Dasmariñas - Olemberio, Jonel G.; A. Poe, Joshua Raphael (11th International Scholars Conference, 2017)
Suicide is an act of killing oneself due to stressful life events and other external factors. It is the second leading cause of death globally among young people aged 15 to 29. This problem must take serious and need a solution. The purpose of this study is to identify the factors on suicidal tendencies among the college students in a private university in Dasmariñas and its relationship to the demographic profile of the respondents namely gender, age, and their respective colleges. The researchers gathered information using survey method. This study utilized the 374 respondents who were selected randomly to answer the questionnaire. The instrument used in the study has is modified questionnaire based on Purpose in Life Test with 44 items scaled from 1 to 5. An Exploratory Factor Analysis (EFA) with a varimax rotation was used to identify the factor on suicidal tendencies among college students. Six factors, with alpha greater than .70, were revealed namely suicidal ideation, negative self-evaluation, social anxiety, vices, hopelessness and helplessness. A Chi-square analysis found that there is a significant relationship between college and social anxiety, gender and vices, college and vices, college and hopelessness, and, college and helplessness. The researchers recommend to the Campus Administration and Student Wellness Center (SWC) to create programs in line with the suicidal factors found. Also, the researchers suggest to the SWC to use their questionnaire as reinforcement on their assessment tools for further investigation.